1 ) Ta có : \(2n^2+3n+3\)
\(=2n^2-n+4n-2+5\)
\(=n\left(2n-1\right)+2\left(2n-1\right)+5\)
\(=\left(n+2\right)\left(2n-1\right)+5\)
Để \(2n^2+3n+3⋮2n-1\)
\(\Leftrightarrow\left(n+2\right)\left(2n-1\right)+5⋮2n-1\)
\(\Leftrightarrow5⋮2n-1\)
Do \(n\in Z\Rightarrow2n-1\in Z\)
\(\Rightarrow2n-1\in\left\{1;-1;5;-5\right\}\)
\(\Rightarrow2n\in\left\{2;0;6;-4\right\}\)
\(\Rightarrow n\in\left\{1;0;3;-2\right\}\)
Vậy ...
Bài 2 :
a ) \(3x^2-3y^2+4x-4y=3\left(x^2-y^2\right)+4\left(x-y\right)=3\left(x-y\right)\left(x+y\right)+4\left(x-y\right)\)
\(=\left(x-y\right)\left[3\left(x+y\right)+4\right]=\left(x-y\right)\left(3x+3y+4\right)\)
b ) \(12x^2-3xy+8x-2y\)
\(=3x\left(4x-y\right)+2\left(4x-y\right)\)
\(=\left(3x+2\right)\left(4x-y\right)\)
c ) \(x^3+x^2y-x^2z-xyz\)
\(=x^2\left(x+y\right)-xz\left(x+y\right)\)
\(=\left(x^2-xz\right)\left(x+y\right)\)
\(=x\left(x-z\right)\left(x+y\right)\)
d ) \(xy+y-2x-2\)
\(=y\left(x+1\right)-2\left(x+1\right)\)
\(=\left(y-2\right)\left(x+1\right)\)
e ) \(x^3-3x^2+3x-9\)
\(=x^2\left(x-3\right)+3\left(x-3\right)\)
\(=\left(x^2+3\right)\left(x-3\right)\)
1.\(\left(2n^2+3n+3\right):\left(2n-1\right)=n+2\) dư 5 (đoạn này bạn tự chia nha)
Muốn \(2n^2+3n+3\)\(⋮2n-1\) thì \(5⋮2n-1\)
\(\Rightarrow2n-1\inƯ\left(5\right)\)
\(\Rightarrow2n-1=\left\{-5;-1;1;5\right\}\)
\(\Rightarrow2n=\left\{-4;0;2;6\right\}\)
\(\Rightarrow n=\left\{-2;0;1;3\right\}\)
bài 2 nhờ Nguyễn Thanh Hằng hay Mysterious Person giải nha
tui đi học rồi